Input of exome sequencing in early‐onset cerebral amyloid angiopathy - Lou Grangeon; Camille Charbonnier; Stéphane Rousseau; Anne Claire Richard; Olivier Quenez; Aline Zarea; Anne Boland; Robert Olaso; Jean‐François Deleuze; CAA study group; Elisabeth Tournier‐Lasserve; Gael Nicolas; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Genetics of cerebral amyloid angiopathy (CAA) remains understudied. METHODS We assessed variants in Alzheimer's disease (AD) risk factor genes and differential diagnosis genes by performing exome sequencing among 78 patients with early‐onset definite or probable CAA, after negative screening for APP mutation or duplication. RESULTS Among 14 genes involved in non‐Aβ CAA, or vascular leukoencephalopathies, we detected pathogenic NOTCH3 variants in two patients, who exhibited lobar hematomas at the ages of 58 and 65, leading to a diagnosis redirection toward CADASIL. Of the remaining 76 patients, 23.1% carried at least one apolipoprotein E (APOE) ε2 allele and 43.6% carried at least one APOE ε4 allele, known as CAA risk factors. A total of 15 out of 76 (19.7%) carried either a loss‐of‐function or a rare predicted damaging missense or known AD risk variant in SORL1, TREM2, ABCA7, ABCA1, and ATP8B4. DISCUSSION Exome sequencing allowed the redirection toward CADASIL in two patients and suggested shared genetic factors between AD and CAA, beyond the APOE gene. Highlights The genetic component of cerebral amyloid angiopathy (CAA) remains understudied. Rare differential diagnoses such as CADASIL should be considered, even in cases of cerebral hemorrhage. Our study suggests shared genetic factors between AD and CAA, beyond the APOE gene. Rare variants in SORL1, TREM2, ABCA7, ABCA1 and ATP8B4 might be susceptibility factors in early‐onset CAA.,